2017
DOI: 10.1111/vco.12343
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of CD45 negative T cells (T zone cells) in older Golden retriever dogs

Abstract: T zone lymphoma (TZL) is characterized by the clonal expansion of T cells lacking expression of the pan-leukocyte antigen CD45 (TZ cells). A strong breed predisposition is observed in Golden retrievers. This study aimed to confirm aberrant CD45 mRNA expression and determine if Golden retrievers without clinical lymphoma have an increased frequency of circulating TZ cells. Gene expression analysis on confirmed TZL cases showed a significant decrease in CD45 expression compared to normal dogs. Peripheral blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The PCR products in the 420 range (black) were amplified with V gamma 3 primer. 8 Approximately 10 d after aspirates were acquired, biopsies of the cranial mediastinal mass, liver, gastrointestinal tract, mesenteric and prescapular lymph nodes, and spleen were obtained for evaluation and fixed in 10% neutral-buffered formalin. Tissues were routinely processed and paraffin-embedded, and tissue sections of 5-μm thickness were cut and stained with hematoxylin and eosin.…”
mentioning
confidence: 99%
“…The PCR products in the 420 range (black) were amplified with V gamma 3 primer. 8 Approximately 10 d after aspirates were acquired, biopsies of the cranial mediastinal mass, liver, gastrointestinal tract, mesenteric and prescapular lymph nodes, and spleen were obtained for evaluation and fixed in 10% neutral-buffered formalin. Tissues were routinely processed and paraffin-embedded, and tissue sections of 5-μm thickness were cut and stained with hematoxylin and eosin.…”
mentioning
confidence: 99%
“…Clinicians should combine data from the physical examination, clinical course, and biological behavior of the tumor, as well as results of flow cytometry and histopathology before making a final diagnosis of TZL. A recent study also suggested that PARR could be more sensitive than flow cytometry when the clonal cells still account for a minority of the lymphocyte population . In this study, a clonal T‐cell receptor gamma locus rearrangement was found in 34% of “healthy” Golden Retrievers with circulating T‐zone cells, and no clinical evidence of lymphoma or another lymphoproliferative disease .…”
Section: Discussionmentioning
confidence: 48%
“…A recent study also suggested that PARR could be more sensitive than flow cytometry when the clonal cells still account for a minority of the lymphocyte population . In this study, a clonal T‐cell receptor gamma locus rearrangement was found in 34% of “healthy” Golden Retrievers with circulating T‐zone cells, and no clinical evidence of lymphoma or another lymphoproliferative disease . Since the Golden Retriever breed is predisposed to develop TZL, Hughes et al.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…4 Hughes et al also enlightened that the immunophenotype of TZL is unique in that "the neoplastic T cells do not express the pan-leukocyte antigen CD45, allowing for a reliable diagnosis by immunophenotyping." 8 Our goal with this case report was to emphasize the necessity to dig deeper and combine diagnostics such as flow cytometry and histopathology to reach an accurate diagnosis in puzzling cases. We acknowledge that a lymph node biopsy can sometimes be both a technical and financial hurdle, and this procedure is not offered as part of our standard workup for more straightforward lymphoma patients.…”
mentioning
confidence: 99%